The Role of Elementary School Teachers in Developing Moral Values ​​and Character: Psychological, Sociological and Anthropological Perspectives - Anjura, Delia; Firdaus, Prasetyo Ananda; Gusniardy, Syauqi Robby Bilhard; Azzahirah, Salsabila; Yatri, Ika; Nawawi, Muhammad Azhar (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
In elementary school, instilling moral values and character is an essential part of education to produce a moral and responsible individual. This article examines psychology, sociology, and anthropology from the perspective of elementary school teachers in building students' character. From a psychological point of view, teachers serve as examples of the primary roles that influence students' morality through their daily interactions. Anthropology looks at how cultures shape standards of moral behavior, while educational sociology points out how important an inclusive classroom environment is to support learning social values. In this study, a qualitative descriptive approach is used as a methodology for the study of literature. It shows that developing a strong morality and character thus requires a multidisciplinary approach that integrates a variety of disciplines. This article combines these theories to give an in-depth view of moral education in elementary schools.